Associations, Christ groups, and their place in the Polis - Kloppenborg, John S. (Zeitschrift für die neutestamentliche Wissenschaft, 2017)
Early Christ groups, like Greek and Roman associations, engaged in mimicry of various civic institutions, and for similar reasons: to facilitate the integration of sub-altern groups into civic structures; to create “communities of honour” in which virtue was recognized and rewarded; and to produce small social structures in which the democratic values of autonomy could be performed. While mimicking civic structures, early Christ groups also displayed in varying ways ambivalence toward the city, either declaring themselves to be “resident aliens” or claiming to belong to a different polity.